Inter-state and intra-state conflict in global politics from Eurasia to China - Arı, Tayyar, 1960- (Lexington Books, 2021)
"The main purpose of the study is to discuss the inter-state and intra-state conflicts and the main problem areas in the geography extending from China to Eurasia. The book consists of eighteen chapters, all written by senior professors and associate professors"--